PENGARUH KERAGAMAN PRODUK TERHADAP KEPUASAN KONSUMEN PADA DEPOT MANDARIEN MOESLEM KABUPATEN SITUBONDO DENGAN KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING - Annisa R, Auliyah; Perwitasari W, Dwi; Ediyanto, Ediyanto (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Marketing is an activity that needs to be carried out by a company, be it a company of goods or services in an effort to maintain the survival of its business. Swasta and Handoko (2011:4) stated that "Marketing is an overall system of business activities that are shown to plan, determine prices, promote, and distribute goods or services that can satisfy the needs of both existing and potential buyers". The purpose of this study was to analyze and test the effect of Product diversity on consumer satisfaction at the Mandarien Moeslem Depot Kabupaten Situbondo with Purchasing decisions as an intervening variable. The population in the study was consumers of the Mandarien Moeslem Depot. The sampling technique is determined by random sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model – Partial Least Square (PLS). Based on the hypothesis test of direct influence using the Smart PLS 3.0 application, the results showed that product diversity has a significant positive effect on purchasing decisions. Product diversity has a significant positive effect on consumer satisfaction. Purchasing decisions have a significant positive effect on consumer satisfaction. Product diversity to consumer satisfaction through purchasing decisions has a significant positive effect.